2017
DOI: 10.1111/nep.12807
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with a decreased estimated glomerular filtration rate based on cystatin C levels in school‐age children with extremely low birthweight

Abstract: CysC-eGFR might already be decreased at school age in children born with ELBW. Renal assessment in regular follow-up examinations is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…In a sample of 422 young adults born before 32 weeks of gestation, 10% had elevated blood pressure and 2.7% had microalbuminuria, as compared to 33.3% with elevated blood pressures and 11.9% with microalbuminuria in the sample described here (38,39). Likely explanations are that the mean gestational age and birth weight were lower in our sample as compared to those studied previously, and the relatively high frequency of African-American (42.9%) and overweight (53.8%) children in our cohort (34,(40)(41)(42)(43)(44)(45)(46). Both overweight status and African-American race are independent risk factors for CKD related to hyperfiltration, obesity related focal segmental glomerulosclerosis, and the genetic predisposition to develop CKD (6,44,47).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In a sample of 422 young adults born before 32 weeks of gestation, 10% had elevated blood pressure and 2.7% had microalbuminuria, as compared to 33.3% with elevated blood pressures and 11.9% with microalbuminuria in the sample described here (38,39). Likely explanations are that the mean gestational age and birth weight were lower in our sample as compared to those studied previously, and the relatively high frequency of African-American (42.9%) and overweight (53.8%) children in our cohort (34,(40)(41)(42)(43)(44)(45)(46). Both overweight status and African-American race are independent risk factors for CKD related to hyperfiltration, obesity related focal segmental glomerulosclerosis, and the genetic predisposition to develop CKD (6,44,47).…”
Section: Discussioncontrasting
confidence: 46%
“…We found that none of the hypothesized neonatal risk factors were associated with the presence of one or more abnormal kidney outcome (microalbuminuria, elevated blood pressures, and/or reduced kidney volume) during adolescence. Yamamura-Miyazaki et al found that a lower 5-min Apgar was associated with decreased cystatin C-estimated glomerular filtration rate in school aged children after preterm birth (46). This could not be assessed here as glomerular filtration rate was not assessed in the ELGAN sample.…”
Section: Discussionmentioning
confidence: 89%
“…Following the search strategy described, 248 (232 + 16) hits were analyzed to result in 6 case-control and 3 ELBW cohort studies for the analysis (Figure 1). The key characteristics of the individual case-control studies are provided in Table 1 [12][13][14][15][16][17][18], cohort studies in Table 2 [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Following the search strategy described, 248 (232 + 16) hits were analyzed to result in 6 casecontrol and 3 ELBW cohort studies for the analysis [Figure 1]. The key characteristics of the individual case-control studies are provided in Table 1 [12][13][14][15][16][17][18], cohort studies in Table 2 [19][20][21]. Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 19 January 2020 doi:10.20944/preprints202001.0213.v1…”
Section: Resultsmentioning
confidence: 99%
“…Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 19 January 2020 doi:10.20944/preprints202001.0213.v1 Figure 2. Mean or median (estimated) glomerular filtration rate (eGFR) in the 6 case-control studies over age (years) [12][13][14][15][16][17]. The arrows connect the same cohort assessed at the age of 7 and 11 years respectively [17,18] (ELBW: extreme low birth weight).…”
Section: Discussionmentioning
confidence: 99%